Imaging the Hydrothermal System of Kirishima Volcanic Complex With L‐Band InSAR Time Series. Issue 11 (9th June 2021) - Yunjun, Zhang; Amelung, Falk; Aoki, Yosuke
Abstract: We present deformation measurements of the Kirishima volcanic complex from ALOS and ALOS‐2 Interferometric Synthetic Aperture Radar (InSAR) time series during 2006–2019. Shinmoe‐dake deflated ∼6 cm during the 2008–2010 phreatic eruptions and inflated ∼5 cm prior to the 2017 magmatic eruption. Iwo‐yama inflated ∼19 cm within the crater since January 2015 and ∼7 cm around the southern and western vents since 4 months before the 2018 eruption. These deformations can be modeled as ellipsoids at ∼700 m depth beneath Shinmoe‐dake and as a sphere on top of an ellipsoid at ∼130 and ∼340 m depths beneath Iwo‐yama. Combining geodetic, geoelectric, geochemical, and petrological analysis, we interpret the hydrothermal origin of the deflation at Shinmoe‐dake and inflation at Iwo‐yama; the hydrothermal–magmatic transition during the 2011 Shinmoe‐dake eruption; and water‐boiling and bottom‐up pressurization as driving mechanisms of the inflation at Iwo‐yama. The study highlights the imaging potential of InSAR time series on complex hydrothermal systems. Plain Language Summary: Steam‐blast eruptions are driven by the heat of magma interacting with water. Although small in size, they are very common and unpredictable, making them hazardous. In order to know when and where these interactions started and how they led to the eruption, we take the Kirishima volcano group as an example and use 10 years of satellite radar images to measure its ground surface deformation. We find that Shinmoe‐dake fell ∼6 cm during the 2008–2010 eruptions, much earlier than previously thought; while Iwo‐yama rose ∼7 cm since 4 months before its 2018 eruption. Combining models from specialized computer code with previous studies from other disciplines, we explain that the fall of Shinmoe‐dake and the rise of Iwo‐yama are due to the steam release and water accumulation of water‐rich zones at ∼700 and ∼340 m depth below the surface, respectively. The water‐rich zone of Shinmoe‐dake was replaced and filled by magma during the 2011 eruption. These short‐lived, small‐size deformations have not been identified in the region before nor has the type of deformation in general been studied extensively worldwide. Future volcano monitoring efforts should take this into account on a regular basis. Key Points: Shinmoe‐dake's hydrothermal system deflated during the 2008–2010 eruptions, then was replaced by a magmatic body during the 2011 eruption Persistent inflation at the Iwo‐yama crater during 2014–2019 is driven by liquid–gas two‐phase water boiling Precursory expansion of Iwo‐yama's southern and western vents after December 2017 is driven by the upward migration of magmatic fluid